Basic Necessities to Luxury Living: The Crucial Role of House Plans in Modern Construction Practices - Swati Pandey (International Journal of Rural and Regional Development, 2024)
In order to distinguish them from Individual & houses, buildings that contain many individual dwelling units are frequently referred to as apartment buildings or block apartments. Apartments can be built around courtyards or as rectangular blocks surrounded by a space of varied proportions. buildings can also be built in pairs (semi-conducted), in terraces and all but two buildings having others on either side. Homes that were initially constructed as a single residence can eventually be divided into studios or bedsitters, or they may be adapted for a different use, such as an office or a shop. Early conceptualizations were built to meet only the most basic necessities, but today's lifestyle has evolved as everyone wants to live in luxury. In light of these various components, careful preparation is now essential. Without thoughtful preparation, no construction can be built. Construction of all types of structures is guided by construction drawings used by contractors and builders. Building guidelines can also be helpful for creating project budgets and cost estimates. Building guidelines provide a visual picture of a structures completed appearance. A dwelling plan serves multiple purposes, including displaying both the house design and the finished result. Many people don't consult architects when they need plans for houses because they think they are irrelevant, particularly when they only would like to build their tiny dream home on an isolated piece of land. Importance of a house Plan and many readers disclosed to me that they were unaware of how crucial these documents were. In fact, many admitted that their bodies had always assumed that house plans were only for wealthy individuals who could afford them or those planning the construction of bigger houses (3 bedrooms and up) or stored homes. Therefore, when I highlighted the purposes of a house plan, many who intended to put up their basic one-bedroom homes did not think that significant.
Keywords: Building; Environments; Planning; Space planning; construction